BIOLOGY OF LIONURUS TURKESTANIUS DISTRIBUTED IN SURKHANDARYA REGION - Rakhimova Sevara Turayevna (Journals Park Publishing, 2022)
The article provides information about the distribution of the leonurus plant, its species, and where it can be found in Uzbekistan. Medicinal properties of the Leoburus plant and its healing properties for which diseases are shown. Brief information on the distribution of this plant in the Surkhandarya region is given.
Keywords: Leonurus, medicinal plant, folk medicine, sedative, vegetable oil, amino acids.